On desperate ground the Marines at the reservoir, the Korean War's greatest battle - Sides, Hampton (New York Doubleday, 2018)
"A chronicle of the extraordinary feats of heroism by Marines called on to do the impossible during the greatest battle of the Korean War."--Provided by publisher.
Includes bibliographical references (pages 345-378) and index.
Keywords: United States. -- Marine Corps. -- Marine Division, 1st -- History; Korean War, 1950-1953 -- Campaigns -- Korea (North) -- Changjin Reservoir; Changjin Reservoir (Korea) -- History, Military -- 20th century